Indicadores bibliométricos da produção científica dos Programas de Pós-Graduação em Educação Física do Centro-Oeste: uma análise epistemológica da subárea pedagógica - Jorge, Antônio Chadud (2023)
It is known that the Stricto Sensu Graduate Program in Brazil is very recent compared to other parts of the world, in the 1930s the first actions on the subject began with the Statute of Brazilian Universities, then only in 1965 with the opinion Sucupira é that Stricto Sensu Postgraduate Studies were effectively regulated in our country, however political and financial autonomy only materialized in 1975 with the first National Postgraduate Plan. The first graduate program in physical education in Brazil was created at USP in 1977, then at UFSM in 1979, shortly after at UFRJ in 1980, from these several were created in the 80s, but all in the south and southeast regions only in 1998 the first program outside these two regions was created, the UCB PPGEF in the midwest region. In 2012, Professor Michele Sacardo published her doctoral thesis on bibliometric studies of the works of the PPGEF and PPGE in the Midwest region that dealt with physical education, taking into account works published until 2010. Knowing that the PPG are the highest level of production within a scientific field,it was decided as the general objective of this work, to build indicators of scientific production in the field of Physical Education, based on dissertations and theses linked to the Postgraduate Programs in Physical Education (PPGEF) in the Midwest , which dealt with questions about the pedagogical subarea. A mixed type of research (quali/quanti) was constructed, in which Bibliometrics/Scientometrics was used to achieve our objectives in order to build the desired metrics and identify the works epistemologically/methodologically.In addition to the analyzes based on the indicators, the IRAMUTEq software was used to build a word cloud and analyze similarities that contributed to achieving the proposed objectives. It is concluded with this work that the indicators about the scientific production in the area of Physical Education from the PPGEF of the Midwest in relation to the pedagogical subarea, remain inferior to the other subareas, mainly in comparison with the subarea of biodynamics, even so it was it is possible to verify a small advance in relation to the previous period, which is very positive for the scientific field of physical education.